Effect of cation doping on the structure of hydroxyapatite and the mechanism of defluoridation. Issue 6 (15th April 2018) - Chen, Zhenzhen; Liu, Yiling; Mao, Lianzhen; Gong, Lianyuan; Sun, Wenjin; Feng, Li
Abstract: The structure of three cation-doped hydroxyapatite filter materials with different cation radii and valence states, aluminum-doped hydroxyapatite (Al-HA), magnesium-doped hydroxyapatite (Mg-HA) and lanthanum-doped hydroxyapatite (La-HA), were studied to explore the performance and possible mechanism of defluoridation by means of Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Scanning electron microscope (SEM)/Energy-dispersive X-ray spectroscopy (EDS), BET and Zeta potential analysis. The results demonstrated that cation doping with different radii could weaken lattice structure of hydroxyapatite, increase content of hydroxyl group and improve exchange ability with fluoride ions. However, the decisive factor affecting the capacity of fluoride removal was valence state of doped ion, because defluoridation capacity of Al-HA and La-HA with trivalent cations were larger than Mg-HA with bivalent cation. In addition, other studies related to the process of defluorination were carried out. The mechanism of defluoridation mainly included physical adsorption and chemical adsorption. First, F - was deposited on the surface of the filter material by physical adsorption. After F - diffused into the voids of the filter interval, and underwent ion exchange and complexation with -OH functional group in the lattice. Cation-doped hydroxyapatite structure and mechanism of fluoride removal were of great significance in the field of environmental governance.